Early childhood learning patterns for a home visiting program in rural China. Issue 2 (14th May 2022) - Zhou, Jin; Heckman, James; Wang, Fuyao; Liu, Bei
Abstract: This paper uses novel experimental data from a prototypical early childhood home visiting program in China with high‐frequency measurements to investigate the growth of multiple skills. After identifying the presence of child skill development on multiple skills during the intervention, we further study the features of child learning patterns. We find that individual heterogeneity and previous task performance (state dependence) are key properties of the child's task performance during the intervention, consistent with models of reinforcement learning.